2005
DOI: 10.1519/15314.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Creatine Loading With or Without Carbohydrate on Repeated Bouts of Maximal Swimming in High-Performance Swimmers

Abstract: The addition of carbohydrate (CHO) to an acute creatine (Cr) loading regimen has been shown to increase muscle total creatine content significantly beyond that achieved through creatine loading alone. However, the potential ergogenic effects of combined Cr and CHO loading have not been assessed. The purpose of this study was to compare swimming performance, assessed as mean swimming velocity over repeated maximal intervals, in high-performance swimmers before and after an acute loading regimen of either creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
2
8
0
3
Order By: Relevance
“…However, these subjects were much younger, highly trained, and exercised at a much higher intensity that the subjects in the current study. In a study that augmented Cr supplementation with carbohydrates, Theodrou et al (39) reported there was no added advantage to the carbohydrate plus Cr supplemented group when compared to the Cr only group concerning maximal swim times.…”
Section: Discussionmentioning
confidence: 99%
“…However, these subjects were much younger, highly trained, and exercised at a much higher intensity that the subjects in the current study. In a study that augmented Cr supplementation with carbohydrates, Theodrou et al (39) reported there was no added advantage to the carbohydrate plus Cr supplemented group when compared to the Cr only group concerning maximal swim times.…”
Section: Discussionmentioning
confidence: 99%
“…A escolha pela modalidade da natação foi feita por este ser um exercício de endurance, que mobiliza a maioria das articulações do corpo 18 e promove a frequente utilização de músculos da perna tais como o sóleo e o gastrocnêmio, uma vez que os animais devem realizar a flexão plantar para se manterem na superfície da água.…”
Section: Discussionunclassified
“…Além disso, as baixas concentrações desse composto encontram-se entre um dos limitantes do desempenho em atividades de curta e alta intensidade 16 . Alguns trabalhos apontam melhoras na propulsão bruta e na eficiência da propulsão sem alteração na composição e peso corporal de nadadores suplementados com creatina 17 , por outro lado, alguns não acreditam no potencial ergogênico da creatina pois não observaram em seus trabalhos melhoras na performance e/ou composição corporal [18][19] . De modo geral, o músculo esquelético tem a capacidade de se adaptar aos diferentes tipos de treinamento e estes, muitas vezes, estão associados às estratégias advindas de recursos ergogênicos, que somados podem ser o diferencial para a conquista do lugar mais alto do pódio.…”
Section: Introductionunclassified
“…Isto poderia explicar a alteração ocorrida no grupo controle treinado, sem suplementação de Cr (G2). A natação como modelo de atividade física em ratos é amplamente descrita na literatura (THEODOROU et al, 2005;MORIFUGI et al, 2005;ANOMARISI et al, 2004). Neste estudo foi utilizado um protocolo de treinamento de resistência aeróbica, já empregado por Souza (2006) et al (1996).…”
Section: Estesunclassified